(untitled) (Sustainability in Debate, 2024)
This article analyses the conflicts and the structure of water governance in the Paraguay River Basin – South America – based on a review of documentary sources, specialised literature, and interviews with key stakeholders operating in the basin. The study shows that the internal asymmetry of Brazil and between this country and Paraguay is crucial in the definition of water use in the Basin, thus resulting in conflicts. The results of the study highlight the need for advances in the implementation of agreements for the basin and the fact that these should include instruments that encompass new scales of management and cooperation opportunities from local stakeholders, who have been neglected in decisions despite the coexistence of informal agreements between the parts.